Active versus passive screen time for young children - Wyeth, P; Sweetser, P; Ozdowska, A; Johnson, D (My University, 2012)
In this paper, we report some initial findings from our investigations into the Australian Government’s Longitudinal Study of Australian Children dataset. It is revealed that the majority of Australian children are exceeding the government’s Screen Time recommendations and that most of their screen time is spent as TV viewing, as opposed to video game play or computer use. In light of this finding,we review the body of research surrounding children’s engagement in Screen Time activities and the associated positive and negative effects. Based on existing evidence,we define two categories of Screen Time—Active Screen Time and Passive Screen Time. It is proposed that this distinction provides a more accurate classification of Screen Time and a more informative lens through which to consider the associated benefits and detrimental effects for young children.
Keywords: Child Development; Education and Training -- Time Use; Health; Children -- Outcomes; Activities -- Children's activities; Health and wellbeing; Childhood and child development; Learning, education and training; Child Development; Children; Education and Training; Activities; Health; Time Use; Outcomes; Children's activities; Health and wellbeing; Childhood and child development; Learning, education and training